Identifikasi Kebutuhan Ruang Terbuka Hijau Jalur Jalan dan Pulau Jalan di Boyolali - Rina Kurniati (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
The lack of the existence of green open spaces can lead to a decrease in the quality of the urban environment, such as high air pollution, flooding, and an increase in social crises where people have no place to interact. Although green open spaces have a variety of benefits, including social, ecological and aesthetic benefits, these benefits have not been fully felt by the community. Based on this, a policy that can be formulated by the Regional Government is needed to place the problem of providing green open space as one of the important issues in sustainable development programs. This study aims to map the public green open space of road trees and existing road islands and establish plans for the construction of road tree RTH and island roads in Boyolali Regency in a period of 20 years using a qualitative descriptive method. Planning for the construction of RTH for pedestrian way and road divider is carried out by analyzing the minimum area requirements based on the area of the urban area, the projected population in urban areas in 2036, the carrying capacity and capacity of the environment, and the needs of certain functions. As a result, the size of the road component and the median of the road were set at ± 2.97 hectares (0.0125%) of the total urban area of Boyolali Regency, while for the pedestrian way it is ± 1.66 hectares (0.0069%) of the area urban Boyolali Regency. The results of these calculations are to provide direction for the future green open space for road and road divider in Boyolali.